LIVING DATA: TRANSFORMING PEDAGOGY THROUGH NEUROSCIENCE,TECHNOLOGY AND MOVEMENT - Chandrasekaran S (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This paper explores the intersection of neuroscience, technology, and movement through a multidisciplinary approach to teaching and learning in the project titled "Centering the Center." This project reimagines classroom methodologies by using performance art to translate abstract concepts into visual, auditory, and movement-based experiences. By bridging neuroscience, technology, and dance, it offers an innovative model for embodied learning that engages both cognitive and sensory understanding. A central element of the project is the use of real-time brain mapping technologies to track neural activity during performances. The resulting data points are transformed into dynamic learning experiences, enabling learners to engage in immersive and participatory educational practices. This integration of live data and performance art introduces a novel teaching methodology for multidisciplinary learning.The paper also examines how pedagogical frameworks can shift from traditional educational constructs to sensory engagement through dance movement. This methodology enables learners to translate complex concepts into collective experiences that are both artistically and intellectually stimulating.Through interactive installations, data-driven performances, and immersive virtual experiences, the project presents a multidisciplinary framework that fosters empathy, critical thinking, and the ability to translate abstract knowledge into embodied understanding. This transformative learning approach—where critical reflection, experiential learning, and non-linear discourse converge—expands the boundaries of traditional pedagogy and redefines how we teach, learn, and engage with the complexities of the human condition in the classroom.